2021
DOI: 10.1038/s41467-020-20325-7
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional contact tracing could dramatically improve COVID-19 control

Abstract: Contact tracing is critical to controlling COVID-19, but most protocols only “forward-trace” to notify people who were recently exposed. Using a stochastic branching-process model, we find that “bidirectional” tracing to identify infector individuals and their other infectees robustly improves outbreak control. In our model, bidirectional tracing more than doubles the reduction in effective reproduction number (Reff) achieved by forward-tracing alone, while dramatically increasing resilience to low case ascert… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
111
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(135 citation statements)
references
References 39 publications
6
111
0
Order By: Relevance
“…Test-trace-isolate (TTI) strategies have been widely used to mitigate the spread of SARS-CoV-2 9 . Models by the present authors 10 and others 11 have found that incorporating backwards tracing to identify infector individuals could dramatically increase the efficacy of tracing programs. However, testing delays, mistrust, and low compliance have undermined the confidence of health authorities in the benefits of TTI 12,13 .…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…Test-trace-isolate (TTI) strategies have been widely used to mitigate the spread of SARS-CoV-2 9 . Models by the present authors 10 and others 11 have found that incorporating backwards tracing to identify infector individuals could dramatically increase the efficacy of tracing programs. However, testing delays, mistrust, and low compliance have undermined the confidence of health authorities in the benefits of TTI 12,13 .…”
Section: Introductionmentioning
confidence: 70%
“…In our branching-process model 10 , each case generates a number of new cases drawn from a negative binomial distribution according to pre-specified incubation-and generation-time distributions (Table 1). Cases are identified and isolated based on symptoms alone or through contact tracing.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Averaged over 100 rollouts of the epidemiological simulations, the line represents the sensitivity (true positive rate) and specificity (true negative rate) achieved across operating thresholds of the system. Moreover, in principle, PanCast also allows for the implementation of backward contact tracing (25), where not only contacts of the positively tested individual get traced, but also the contacts of their contacts.…”
Section: Discussionmentioning
confidence: 99%